Hubungan Tingkat Pengetahuan Tentang Covid’19 Terhadap Tingkat Kecemasan Pada Masyarakat Rt 03 Rw 09 Di Desa Buaran Serua Indah - Putri, Suzanna Fabella; Anggraini, Dewi; royani, royani; Irawati, Reni (Jurnal Kesehatan STIKes IMC Bintaro, 2023)
ABSTRACT Introduction: Corona virus or called Coronavirus Disease (COVID-19) is a disease caused by a new type of Corona Virus, Sars-Cov-2. The outbreak was first detected in Wuhan, China on December 11, 2019 and was designated as a global COVID-19 pandemic by the Indonesian Health Organization (WHO) on March 11, 2020. Knowledge is the understanding of a given topic. By having a good knowledge, people's anxiety levels decrease and become mild. Research Objective is to find out the relationship of knowledge levels about COVID'19 to anxiety levels in the RT 03 RW 09 community in Buaran Serua Indah Village. The research method used is a quantitative method, that uses a cross-sectional approach. The study's measuring instrument used questionnaires. The population in this study is a community aged 17-55 years on RT 03 RW 09 in Buaran Serua Indah Village which amounts to 325 respondents, with a sample number of 70 respondents with quota sampling techniques, analysis data using the Chi-Square test. Research Results: Based on research obtained the results of analysis using the Chi-Square test obtained a p value of 0.032 (p value=0,032<0,05) : OR = 2.925. which means that there is a relationship between the level of knowledge about COVID and anxiety levels in the RT 03 RW 09 community in Buaran Serua Indah Village.